Penentuan Kadar Natrium (Na) dan Kalsium (Ca) Pada Air Laut Desa Posona - Burhan Burhan; Suherman Suherman; Paulus Hengky Abram (Universitas Tadulako, 2021)
It has been done a study on the determination of sodium (Na) and calcium (Ca) levels in seawater at Posona Village. The aims of this study were to determine the levels of sodium (Na) and calcium (Ca) in seawater in Posona village. The tools used were an atomic absorption spectrophotometer (AAS) and a flame photometer. Seawater samples were taken in the morning and afternoon in 3 distance points: 50 meters, 100 meters, and 150 meters from the edge of the land surface of the seashore. The level of sodium (Na) was measured at wavelengths of 589 nm while calcium (Ca) at a wavelength of 422.7 nm. The results of the study obtained the sodium levels in the morning samples with a distance of 50 m, 100 m, and 150 m amounted of 18.076 mg/L, 18.395 mg/L, and 18.715 mg/L. While the afternoon samples for the sodium (Na) levels was 18.475 mg/L, 18.742 mg/L, and 18.249 mg/L, respectively. The results of the analysis of calcium levels in the morning samples were 8.431 mg/L, 8.8 mg/L, and 7.661 mg/L, whereas in the afternoon for calcium (Ca) levels were 9.415 mg/L, 9.231 mg/L, and 7.692 mg L, respectively.